Review: Endodontic Bacterial Characterization - Asha Kiran Panda; Bibhuti Prasad Barik (Wolters Kluwer Medknow Publications, 2020)
Microorganisms, more specifically bacteria, are well known for endodontic pathogenesis. The motivation for quick identification of endodontic bacterial species is to inhibit their growth and to reduce the inflammation. Molecular characterization of these pathogens shall surely aid in understanding endodontics, preservation of oral health, and exploration of finest therapeutics. Characterizing endodontic bacteria structurally and functionally is crucial. Approaches such as microscopic, genotypic, and proteomic identification and molecular phylogeny have been effectively realistic to identify rapidly evolving endodontic strains. Developments of high-throughput DNA sequencing practices are believed to be having high success strategies in investigating community genome data following classical approaches. The existing dynamic metagenomic tools may be directed toward the development of innovative systems biology approaches for effective one-to-one therapeutic strategies.